2022
DOI: 10.3389/fcvm.2022.789729
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C May Improve Left Ventricular Ejection Fraction: A Meta-Analysis

Abstract: BackgroundVitamin C deprivation can lead to fatigue, dyspnea, oedema and chest pain, which are also symptoms of heart failure (HF). In animal studies vitamin C has improved contractility and mechanical efficiency of the heart. Compared with healthy people, patients with HF have lower vitamin C levels, which are not explained by differences in dietary intake levels, and more severe HF seems to be associated with lower plasma vitamin C levels. This meta-analysis looks at the effect of vitamin C on left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 87 publications
(141 reference statements)
1
11
0
Order By: Relevance
“…However, refuting their conclusion does not explain the lack of observed benefit during the period of intravenous vitamin C administration. This is unexpected given the biological evidence and previous findings [1][2][3][4][5][8][9][10][11][12][13]. Nevertheless, there are a few potential explanations.…”
Section: Lack Of Benefit During Vitamin C Administrationmentioning
confidence: 77%
See 1 more Smart Citation
“…However, refuting their conclusion does not explain the lack of observed benefit during the period of intravenous vitamin C administration. This is unexpected given the biological evidence and previous findings [1][2][3][4][5][8][9][10][11][12][13]. Nevertheless, there are a few potential explanations.…”
Section: Lack Of Benefit During Vitamin C Administrationmentioning
confidence: 77%
“…Vitamin C deficiency increases the risk of pneumonia and there are indications that vitamin C could be beneficial against pneumonia [ 8 ]. Sepsis is often associated with myocardial dysfunction [ 6 , 7 ], and meta-analyses indicate that vitamin C may protect the heart when under stress [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The classification of the remaining 24 cases is not clear. In controlled trials, vitamin C has influenced left ventricular ejection fraction (LVEF) [ 130 ], which indicates that vitamin C can have effects on LV function. Controlled trials have also shown that vitamin C can influence pulmonary function tests [ 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…), and α-lipoic acid (0.6 g) for 30 days exerted beneficial effects on macrovascular function in patients with HFrEF ( Bunsawat et al, 2020 ). A recent meta-analysis also revealed that vitamin C administration augmented LVEF in heart failure patients ( Hemilä et al, 2022 ). The findings suggest that supplemental vitamin C may afford synergistic effects with sacubitril/valsartan if given together in patients with heart failure.…”
Section: Mechanistic Roles Of Sacubitril/valsartan In Cardiac Remodelingmentioning
confidence: 99%